PEMBELAJARAN MENULIS KARANGAN DESKRIPSI SISWA SEKOLAH DASAR MELALUI TEKNIK OBJEK LANGSUNG - Mayrita, Hastari (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
Writing skills is one of the language skills that must be possessed by the students. Writing can help students to express, express ideas or opinions, thoughts, and feelings that are owned. Teachers should have the ability to use the methods, techniques, or strategies in order to motivate students to develop their intellect and creativity in writing. One technique that can be used to stimulate students in skilled and delighted in learning to write particular essay is a description of the application of techniques direct object. The application of this technique is expected to help students, especially new students in elementary school to learn in ideas that has, thus motivating them later for skilled and enjoys writing activities early on.